Analisis Kinerja Manajemen PT Sariguna Primatirta Tbk. Menggunakan Metode Balanced Scorecard Periode 2018-2020 - Mohammad Khoiruzi Afiq; Helmina Ardyanfitri (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
The high demand for quality drinking water in Indonesia, at least Indonesia needs 570.40 million liters every day. PT Sariguna Primatirta Tbk is a drinking water producer with the first producer in Indonesia to receive a food safety management ISO 22000: 2005 certificate and has a Top Brand Index 2021 achievement of 39.7% with the first rank in the Oxygenated Bottled Drinking Water category. Management performance appraisal is important not only for internal, but also for the government, investors and the general public. This assessment can be used as a tool used to assess the level of efficiency and effectiveness of management in implementing strategies and preventing company losses. This study aims to determine the management performance of PT Sariguna Primatirta Tbk for the 2018-2020 period using the Balanced Scorecard method. The method used in this research is descriptive quantitative research. The object of this research is the Financial Statements of PT Sariguna Primatrita Tbk for 2018-2020. The results of this study indicate that the performance of PT Sariguna Primatirta Tbk in 2018 to 2019 is categorized as good by getting a total score of 16. However, in 2019 to 2020 there was a decline in performance due to non-optimal use of all assets to generate company profits but still got a total score of 10.